EFEKTIVITAS PROGRAM SMART AUDITING DI KANTOR INSPEKTORAT KOTA MAKASSAR - Irma, Nur; Madani, Muhlis; Nasrulhaq, Nasrulhaq (Universitas Muhammadiyah Makassar, 2022)
ABSTRACTThe purpose of this study was to find out the effectiveness of the smart auditing program at the Makassar City Inspectorate Office. This study used descriptive qualitative, namely an objective description of the state of a program. Thi study used a case study with a total of 6 informants. The results of the study indicated that the Smart Auditing program at the Makassar City Inspectorate Office had run effectively seen from several effectiveness measurement indicators, namely: 1) Program understanding, indicating that the Inspectorate had carried out socialization and provided technical guidance on a regular basis so that the auditors could know the intent and the purpose of launching Smart Auditing. 2) Right on target, it had been effective because with Smart Auditing, auditors couldn carry out audit activities more quickly and thoroughly. 3) On time, in terms of using time more effectively because the completion of the examination could be faster. 4) The achievement of the objectives had not been fully effective because there were still some obstacles that were felt by the auditors. 5) Real changes, the impact of the existence of Smart Auditing was felt by auditors where previously audits that were carried out manually and required energy and time could be completed without having to be in the object of examination (SKPD)Keywords: Effectiveness, Smart Auditing Program